Restriction and Prohibition of Anti-Personnel Mines in International Law - Al- Anzi, Abdul-Salam Housain (Journal of Ecohumanism, 2024)
The topic of "Restricting and Prohibiting Anti-Personnel Mines in International Law" is precise and branched out in detail, and therefore many international conferences and protocols were held until the signing of the Ottawa Treaty in (1997), which strictly prohibits the use of such weapons. Since then, campaigns have been active to support the implementation of the Convention, and two-thirds of the world's states have signed it, but major powers such as the United States of America, Russia and China have not ratified it. Here, several problems arise, including: How can these states be obligated to respect this Convention, especially with the 1994 Geneva Conventions free of any provision or article pertaining to mine victims, and the commitment of the world's armed groups to respect the Ottawa Treaty, are among the main dilemmas that must be resolved expeditiously.